2018
DOI: 10.1002/bem.22161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 7 T static magnetic fields on the expression of biological markers and the formation of bone in rats

Abstract: In this study, we aimed to evaluate the effects of 7 T static magnetic fields (SMFs) on rat mesenchymal stem cells (MSCs) in order to determine whether strong SMFs affected the osteogenesis of MSCs. MSCs were prepared from bone marrow cells obtained from the femurs of 7-week-old male Fischer 344 rats. MSCs were then combined with b-tricalcium phosphate (b-TCP), yielding two types of TCP/MSC constructs (TCP/P-1 and P-2) on day 0. Exposure was performed for 3 h/day for 6 days, and the experiments were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…In particular, the effect of the magnetic field strength on cells has been a focus of research. As reported, S. Yamaguchi-Sekino, T. Kira, M. Sekino et al found that the differentiation ability of cells was inhibited under the high-intensity magnetic field environment of 7 T [41]. They consider that SMFs may interfere with the opening of ion channels and hinder BMSC osteogenesis.…”
Section: Discussionmentioning
confidence: 87%
“…In particular, the effect of the magnetic field strength on cells has been a focus of research. As reported, S. Yamaguchi-Sekino, T. Kira, M. Sekino et al found that the differentiation ability of cells was inhibited under the high-intensity magnetic field environment of 7 T [41]. They consider that SMFs may interfere with the opening of ion channels and hinder BMSC osteogenesis.…”
Section: Discussionmentioning
confidence: 87%
“… 38 While most studies showed positive effects, Yamaguchi-Sekino et al reported that exposure to 7 T SMF for 3 h/day for 6 days had no effect on the expression of genes and proteins of osteogenic markers of MSCs in tricalcium phosphate (TCP)/MSC constructs. 39 …”
Section: Bone Regenerationmentioning
confidence: 99%
“…In the meantime, magnetic fields have various effects on living organisms ( 5 , 6 , 7 ), but the underlying mechanisms still remain incompletely understood. Similar to other nonliving materials, biological samples may be affected by magnetic torque and/or force in magnetic fields, and one of the most important physical quantities is their magnetic susceptibility, the degree of magnetization in response to an applied magnetic field ( 5 , 8 ).…”
Section: Introductionmentioning
confidence: 99%